Learning by Research: Building Critical Thinking and Analytical Skills in Developing a Scientific Learning Ecosystem - St Fatimah Azzahra; Mahrawi; Maria Teodora A. Loñosa; Abigail Jo M. Abainza (Jurnal Pendidikan Sains Indonesia, 2026)
The low level of critical thinking and analytical skills among students is a rather critical issue. This study aims to analyse the effect of the learning by research model on improving students' critical thinking and analytical skills. The study uses a quantitative approach with a pretest-posttest design on groups that received research-based learning treatment. The instruments used were critical thinking tests and analytical skills tests that had been validated. Data analysis included descriptive statistics, normality tests, homogeneity tests, and multivariate analysis of variance tests to determine the simultaneous effect of the learning model on both dependent variables. Descriptive analysis results showed an increase in the average critical thinking and analytical skills scores after the implementation of learning by research. Normality and homogeneity tests showed that the data met the assumptions of parametric analysis. The Manova test results showed that the learning by research model had a significant simultaneous effect on students' critical thinking and analytical skills (p < 0.05). These findings indicate that research-based learning is effective in developing higher-order thinking skills through investigation, data analysis, and evidence-based argumentation activities